A Bacterial Artificial Chromosome Reporter System for Expression of the Human FOXP3 Gene in Mouse Regulatory T-Cells - Tsuda, Masato; Tone, Yukiko; Ogawa, Chihiro; Nagaoka, Yoshiko; Katsumata, Makoto; Necula, Andra; Howie, Duncan; Masuda, Esteban; Waldmann, Herman; Tone, Masahide (Frontiers in Immunology, 2017)
The transcription factor FOXP3 plays key roles in the development and function of regulatory T cells (Treg) capable of preventing and correcting immunopathology. There has been much interest in exploiting Treg as adoptive cell therapy in man, but issues of lack of nominal antigen-specificity and stability of FoxP3 expression. In order to enable fundamental studies of human FOXP3 (hFOXP3) gene regulation, and to provide preclinical tools to guide the selection of drugs that might modulate hFOXP3 expression for therapeutic purposes, we generated hFOXP3/AmCyan BAC (Bacterial Artificial Chromosome) transgenic mice and transfectants, wherein hFOXP3 expression was read out as AmCyan expression. Using the transgenic mice, one can now investigate hFOXP3 gene expression under defined experimental conditions used for mouse Foxp3 (mFoxp3) studies. Here, we demonstrate that hFOXP3 gene expression in BAC transgenic mice is solely restricted to CD4+ T-cells, as for mFoxp3 gene expression, showing that hFOXP3 expression in Treg cells depends on fundamentally similar processes to mFoxp3 expression in these cells. Similarly, hFOXP3 expression could be observed in mouse T-cells through TCR stimulation in the presence of TGF-b. These data suggest, that at least in part, cell type specific human and mouse foxp3 gene expression is regulated by common regulatory regions which for the human, are located within the 110-kb human FOXP3 BAC DNA. To investigate hFOXP3 gene expression further, and to screen potential therapeutics in modulating hFOXP3 gene expression in vitro, we also generated hFOXP3/AmCyan expression reporter cell lines. Using the reporter cells and transcription factor inhibitors, we showed that, just as for mFoxp3 expression, inhibitors of NF-kB, AP1, Stat5, Smad3, and NFAT also block hFOXP3 expression. hFOXP3 induction in the reporter cells was also TGF-b dependent, and substantially enhanced by an mTOR inhibitor, Torin1. In both the reporter transgenic mice and cell lines, histone H4 molecules in the hFOXP3 promoter and enhancers located in human CNS1 and CNS2 regions were highly acetylated in natural Treg and TCR/TGF-b induced Treg, indicating hFOXP3 gene expression is regulated by mechanisms similar to those previously identified for the mFoxp3 gene.